RUQYAH SEBAGAI PENGOBATAN BERBASIS SPIRITUAL UNTUK MENGATASI KESURUPAN - Alfiyah Laila Afiyatin (UIN Sunan Kalijaga Yogyakarta, 2019)
AbstractThe existence of spiritual involvement in handling possession, this purpose article to describe the implementation of ruqyah possessed by patients in Nashrun Minallah boarding school and spiritual interpretation in the implementation of ruqyah. This type of research is qualitative, with interview and observation research methods. The research subjects are 1 ruqyah and 1 assistant. The results showed that two types of trance experienced by patients were possessed by psychic and physical disorders, the main process in ruqyah was blades, then safeguards developed by patients with independent ruqyah with necessary health assistance. Spiritual has a significant role in the ruqyah process which is carried out to deal with patients suffering from spiritual illness in the form of possession. Keywords: ruqyah, spiritual medicine, possessed.